Association of Traditional Chinese Medicine Use With Adherence to Prescribed Western Rheumatic Medications Among Chinese American Patients: A Cross‐Sectional Survey. Issue 10 (29th September 2020) - Sun, Kai; Szymonifka, Jackie; Tian, Henghe; Chang, Yaju; Leng, Jennifer C.; Mandl, Lisa A.
Abstract : Objective: Chinese Americans are a fast‐growing immigrant group with worse rheumatic disease outcomes compared to white populations and frequently use traditional Chinese medicine (TCM). Whether TCM use is associated with lower adherence to Western rheumatic medications is unknown. The present study was undertaken to examine adherence to Western medications for systemic rheumatic diseases in the Chinese American immigrant population and its association with TCM use. Methods: Chinese Americans actively treated for a systemic rheumatic disease were recruited from 2 Chinatown clinics. Sociodemographic, TCM use, and clinical data were gathered. Self‐reported health status was assessed using Patient‐Reported Outcome Measurement Information System short forms. Adherence was stratified using the 8‐item Morisky Medication Adherence Scale. Factors independently associated with high adherence were identified using multivariable logistic regression. Results: Of 230 subjects, the median age was 55 years (range 20–97 years), 65% were female, 71% had a high school education or less, 70% were enrolled in Medicaid, and 22% reported fluency in English. The most common rheumatic diagnoses were rheumatoid arthritis (41%), systemic lupus erythematosus (17%), and seronegative spondyloarthropathies (15%). One‐half reported TCM use in the past year, and 28% reported high adherence to Western rheumatic medications. In multivariable analysis, high adherence was associated with TCM use (odds ratio [OR] 3.96, P < 0.001), being married (OR 3.69, P = 0.004), medication regimen complexity (OR 1.13, P = 0.004), and older age (OR 1.06, P < 0.001), and was negatively associated with anxiety (OR 0.94, P = 0.001). Conclusion: While adherence to Western rheumatic medications was low in this cohort, interestingly, it was higher among TCM users compared to nonusers. TCM use appears to represent a complementary rather than an alternate approach to disease management for these patients. Future studies should evaluate whether TCM use is associated with better disease outcomes.